Blurred Vision: The Calgary Union Stockyard Issue, 1913–1914 - Foran, Max (Urban History Review / Revue d'histoire urbaine, 2004)
Calgary's historic association with the ranching industry and the increased volume of livestock from mixed farms led municipal leaders to explore the possibility of establishing a union stockyard in the city in 1913–1914. The measures taken to realize this ambition proved futile for several reasons. City leaders could not match their vision with coherence or direction. The result was inadequate consultation with stakeholders, internecine rivalries, and an almost comical sequence of policy changes in which the city's role in the proposed stockyards stance went from coordinator to partner to sole owner. City Council's well-meaning but ill-informed campaign reflected the random approach to civic policy-making that characterized municipal governments of the period.